Pengaruh Motivasi Kerja Guru dan Pelatihan Organisasi Masyarakat dalam Pengembangan Supervisi Akademik terhadap Kinerja Guru SD Negeri Kecamatan Rupat - Rini Ariyanti (Fakultas Dakwah IAIN Jember, 2021)
Teacher performance can be interpreted as the results achieved by a teacher after the teacher carries out obligations based on skills, experience, duration with the output obtained looks good in terms of quantity or quality. Based on the results of interviews with several teachers, researchers. The work motivation shown by the teachers is still not optimal, it is proven that some teachers come late, at lessons 1,2 and lessons 6,7, 8 there are often no teachers teaching, sometimes they are filled with assignments that are not corrected, Some teachers have low motivation due to lack of financial rewards to meet their daily needs. From the results of interviews with the Bengkalis District Elementary School supervisors, information was obtained that the supervision carried out by the principal as a leader, the impact of the low frequency of supervision carried out by the principal and not being sustainable was the presence of teachers who carried out the learning process in a less professional manner. The research approach used in this research is to use ex post facto research, namely after the fact, by taking data by survey. 1) There is a positive and significant influence between work motivation on teacher performance. The higher the work motivation given, the higher the teacher's performance. 2) There is a positive and significant influence between the variables of Academic Supervision on Teacher Performance at SDN Rupat District. The higher the level of leadership that the principal has, the higher the level of performance that the teacher has. 3) There is a jointly significant influence between the variables of Work Motivation and Academic Supervision on Performance at SDN Rupat District. The higher the work motivation and academic supervision owned by the principal, the higher the level of performance possessed by the teacher assuming permanent work motivation.